Phytochemical Screening and Antibacterial Activity Ethanolic Extract of Solanum mauritianum Scop Leaves Against Staphylococcus aureus and Pseudomonas aeruginosa - BR PA, Ayu Meta Sari; Masfria; Sitorus, Panal (International Journal of Science, Technology & Management, 2022)
According to the Karo people, Solanum mauritianum Scop leaves are widely used as traditional medicine, which is used topically to treat sprains, wounds, and bruises because of their high phenol content. The purpose of this study was to identify the content of secondary metabolites (alkaloids, flavonoids, saponins, tannins, steroids, triterpenoids, and glycosides) that inhibit the antibacterial activity of Staphylococcus aureus and Pseudomonas aeruginosa by the diffusion method using paper discs from the ethanolic extract of Solanum mauritianum Scop leaves. The results of phytochemical screening showed that Solanum mauritianum Scop leaves were positive for alkaloids, flavonoids, glycosides, saponins, tannins, and steroids. Results The antibacterial activity test of the ethanolic extract of Solanum mauritianum Scop leaves showed effective results at a concentration of 80 mg/mL on Staphylococcus aureus with an inhibition zone diameter of 14.54 ± 0.13 mm. Meanwhile, Pseudomonas aeruginosa showed effective results at a concentration of 300 mg/mL with an inhibition zone diameter of 15.70 ± 0.09 mm. Both bacteria showed activity in the strong category. Conclusion The ethanolic extract of Solanum mauritianum Scop leaves has antibacterial activity against both test bacteria with a strong category